Comparison of pulmonary functions of thalassemic and of healthy children - Mardjanis Said; Sudigdo Sastroasmoro; Djajadiman Gatot; Bambang Supriyatno; Yovita Ananta (Indonesian Pediatric Society, 2005)
Objectives The aim of this study was to compare some pulmo-nary functions of thalassemic patients and those of normal chil-dren. Factors correlated with lung dysfunction were assessed.Methods This cross-sectional study compared some pulmonaryfunctions of thalassemic patients with those of healthy children.The study was performed in the Department of Child Health, CiptoMangunkusumo Hospital, Jakarta, Indonesia. Pre- and post-trans-fusion hemoglobin levels of the thalassemic subjects were deter-mined. Other data such as chelation therapy and serum ferritinlevels were also obtained. Both thalassemic and control subjectsunderwent routine physical examinations and lung function testsusing an electronic spirometer. Spirometry was repeated threetimes for each subject, and only the best result was recorded.Results Sixty-three thalassemic patients were enrolled, consist-ing of 32 male and 31 female subjects. Healthy subjects consistedof 31 males and 31 females. Most thalassemic patients (46/63)were found to have lung function abnormalities. This was signifi-cantly different from control subjects, of whom most (39/62) hadnormal lung function. Restrictive lung function abnormality was themost common (42/63) observation documented. Serum ferritin lev-els were obtained from 28 male and 29 female thalassemic sub-jects. There was no correlation between percentage from predictedforced vital capacity and serum ferritin levels, whether in male(r=0.191; P=0.967) or female (r =-0.076, P=0.695) thalassemicsubjects.Conclusion Thalassemic patients have significantly lower lungfunction than healthy children. More thalassemic patients had lungfunction abnormalities compared to healthy children. Restrictivedysfunction was the most common finding in the thalassemic group.No correlation was found between lung function and serum ferritinlevels